Alterations in Gut Health, Bone and Inflammatory Biomarkers, and Blood Flow After Three Months of Prune Consumption. (29th May 2020) - Foley, Elizabeth; Akhavan, Neda; Clarke, Holly; Ormsbee, Lauren; Munoz, Joseph; George, Kelli; Siebert, Shalom; Brunner, Joseph; Serda, Abigail; Arjmandi, Bahram
Abstract: Objectives: Inflammation has been shown to play a role in a variety of disease states including osteoporosis and cardiovascular disease. Leaky gut has been implicated in contributing to these inflammatory states. The purpose of this study was to determine the effect of daily prune consumption on inflammatory markers, bone density, and cardiovascular health in an osteopenic male population. Methods: Twenty-eight healthy men between the ages of 55 and 80, whose lumbar spine bone mineral density (BMD) t-score was between −1.0 and −2.5 were randomized to 0, 50, or 100 g of prunes and 450 mg calcium and 800 IU vitamin D daily for three-months. Participants kept daily logs for the assessment of compliance. DXA scan, blood, anthropometrics, blood pressure (BP), BMD, mean arterial pressure (MAP), and resting blood flow (BF) were collected at baseline and at three months. Serum and plasma samples were subjected to ELISA for the assessment of inflammatory markers including C-reactive protein (CRP), tumor necrosis factor- alpha (TNF-α), and interluekin-6 (IL-6). Bone turnover markers included osteoprotegerin (OPG) and the receptor activator of nuclear factor kappa-Β ligand (RANKL). Gut health was assessed by the measurement of serum lipopolysaccharide binding protein (LBS) and zonulin. Blood flow was assessed via strain-gauge plethysmography. Results: All participants were compliant with the daily supplements. Mean baseline total bone mass was 3004 ± 472 g. Pre- and post-treatment data were analyzed (mean ± SD, pre vs post) for body weight (85.7 ± 13.4 vs 84.6 ± 12.9), waist to hip ratio (0.96 ± 0.063 vs 0.97 ± 0.014), resting blood flow (3.07 ± 1.25 vs. 3.92 ± 1.10), and mean arterial pressure (92.7 ± 10.0 vs 91.1 ± 9.5), all at P > 0.05. Conclusions: While statistical comparisons did not reveal any significant changes in this preliminary data set with the addition of prunes to the diet, additional parameters of inflammation, bone density and turnover, and gut health are currently being evaluated. Funding Sources: California Dried Plum Board.